La adivinación en Oedipus de Séneca - Galán, Lía Margarita (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2007)
The study has the purpose to present the motive of rites and ceremonies in Seneca's 0edipus as semantically strong forms, in opposition to the widespread opinion of the criticism that has seen such motives as ornamental and supernumerary. The artalysis includes the scenes of the divination by the fire (empiromancy) and the examination of the immolated animals' viscera (extispicy), and the Tiresias' necromancy in the Creon's speech. The importance of such scenes comes from the complexity of ideas and notions that converge on them: Stoic philosophical matters, the properly italic beliefs in the varied forms of the diuinatio, the oracular tradition, the affirmation of the Roman culture in front of the Greek tradition, the captatio beneuolentiae and the mobilization of the affectus' audience that organize the dramatic effects